World development report 1984 (Washington, D.C. : Oxford University Press, 1978)
The World Development Report 1984 presents the IMF staff's analysis and projections of economic developments at the global level, in major country groups (classified by region, stage of development, etc.), and in many individual countries. It focuses on major economic policy issues as well as on the analysis of economic developments and prospects. It is usually prepared twice a year, as documentation for meetings of the International Monetary and Financial Committee, and forms the main instrument of the IMF's global surveillance activities.
oif 21/05/13, rpm 12/09/13, osa 09/10/13, osa 15/03/19
Reference
Keywords: Underdeveloped areas; Economic development; International economic relations